Regulacje w zakresie prawa karnego w Statucie Sochaczewskim z 27 kwietnia 1377 roku - Herod, Patrycja Ewa (Saeculum Christianum. Pismo Historyczne, 2016)
This article is the first comprehensive overview of the criminal regulations of the first Statute of Mazovia, which was announced by Prince Siemowit III of Masovia on April 27, 1377 in Sochaczew. The authoress examines 11 criminal laws, which cover more than half of the act. The article presents the legal and penal regulations concerning: the conditions of taking revenge, villainy (robbery and persistent thievery), broadly defined rape on a person, the amount of were-gild for murdering a Włodyka (a representative of lower knighthood) and a well-to-do peasant, complicity, the defamation of people of high rank (ie. the rebuke of nobility), the requirements on which one can exonerate themselves in court, as well as the amount of compensatory damages for beating or wounding a well-to-do peasant. While discussing specific legal articles, the authoress explains the basic notions concerning mazovian criminal law both substantive and procedural, in particular: the penalty of proscription, a vendetta, the penalty of infamy, the rebuke of nobility, exoneration, were-gild and punitive damages. At the same time, the article presents the issue of the death penalty and confiscation of one’s property, which were the most severe penalties for convicted criminals. The article concludes with the summary of the conducted research.